Exploring the model for multimedia messaging services for special context - Grace, H.H.; Kajanthy, S.; Dilogini, S.; Shivany, S. (Proceeding of the International Conference on Advanced Marketing , Vol. 1, 2017, pp. 16-26, 2017)
This research paper aims to explore a model for multimedia messaging services in contemporary marketing environment. There are many research studied in foreign countries regarding Multimedia Messaging service which is applicable to their cultural environment and context. But in Sri Lanka, there are lack of research studies regarding MMS marketing. This research study aims to fill this research gap and to establish a new model for the special context. Now-a-days marketers have reduced the paper advertisement, television advertisement and have shifted to mobile marketing. Mobile usage is an instant response giver to the marketers by the customers. In this way new methods of MMS are making business activities very much effective trends than past eras used on traditional methods. The main purpose of this research paper from the researchers’ point of view is to develop a model to understand the significant role of MMS in contemporary marketing world. This research paper explores a model which gives a new insights of multimedia messaging service connected with marketing aspect to special context through analyzing the past researchers’ conceptual models. This research paper is concluded by citing the past researchers’ models and suggestions. Finally the researchers have found a new model for a special context
Keywords: Ease of use; Intention; MMS; Special context